Esse boom é nosso?: discursos sobre transição capilar na publicidade de cosméticos - Mayra Bernardes Medeiros de Carvalho (2019)
This research aims to investigate, in a communicational perspective, the natural hair journey as an identity politics for black women and its association with hair cosmetics advertising. The general purpose of the research is to understand how the intersections between Seda's – Unilever's hair cosmetics brand – advertising discourses and curly-haired youtubers self-acceptance discourses are settled, observing which values and representations of femininity arise in these interactions. As main methodological procedures, we developed the analysis of Seda Boom's YouTube ads through descriptive charts, followed by the identification of the values and portrayals found on each video's through the observation of the most frequent and meaningful elements of each advertisement. The results point to a significant transformation in the ways to portray black women in hair cosmetics ads, going from the aversion to the appreciation of curly and kinky hair. However, it was also noted that some values and regulatory aesthetic standards remain valid for black women, going against the emancipatory discourse defended by the youtubers elected as brand ambassadors.